Japanese American incarceration : the camps and coerced labor during World War II - Hinnershitz, Stephanie, 1984- (Politics and culture in modern America., 2021)
"Japanese American Incarceration argues that the incarceration of Japanese Americans created a massive system of prison labor that blurred the lines between free and forced work during World War II"--